(untitled)
During the years 1997-1998 an in-field evaluation was made of the effects of transgenic corn on non-target arthropods and on soil fauna. Coleoptera Carabidae, typical soil fauna, were studied and a comparison made of their community structures and degree of specific biodiversity in transgenic and isogenic corn crops. The taxa normally present on corn plants, particularly Aphididae and Cicadellidae, Aranea and Coleoptera (Chrysomelidae, Coccinelidae, Staphilinidae), and other insects living in dose contact with these or with the European Corn Borer (Ostrinia nubilalis), such as Hymenoptera parasitoids and Diptera Syrphidae, were considered as aerial fauna. The statistica